Comparative accuracy of various modes of ultrasonography in the diagnosis of lymph nodes in head and neck region-A prospective study - Subharina Mahapatra; Manjula Hebbale; Amit Mhapuskar; Rajshekhar Halli; J Visshishta; Simran S Singh (Wolters Kluwer Medknow Publications, 2023)
Background: Imaging is crucial for diagnosing head and neck pathologies, particularly those involving lymph nodes (LNs). Ultrasound can detect nodes even smaller than 2 mm in diameter. Objectives: The objectives were to assess the accuracy of the ultrasonography (USG) findings in differentiating malignant and non-malignant LNs. Materials and Methods: Forty patients with clinically palpable LNs in the head and neck region were assigned to either of the two groups based on the inclusion criteria. All the patients were subjected to greyscale sonography, then USG Doppler and USG elastography, and finally, USG-guided FNAB. All the data were tabulated for statistical analysis. A Chi-square test was used. Sensitivity, specificity, positive predictive value, and negative predictive value were calculated. Results: In this study, sensitivity for greyscale USG was 82.8%, whereas sensitivity for USG doppler and USG elastography was 72.2% and specificity for greyscale USG, doppler, and elastography was 88.8%. Conclusion: USG Doppler and USG elastography can be used in conjunction with greyscale USG with high sensitivity and specificity to diagnose soft tissue pathology, particularly in the LNs of the head and neck regions.